2022
DOI: 10.1071/cp21146
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of biochar and NPK on wheat crops under different management systems

Abstract: As a multi-beneficial amendment, biochar is very useful to be applied for improving soil health and crop productivity. Therefore, this study was carried out to assess the influence of wood biochar and mineral nitrogen (N), phosphorus (P) and potassium (K) fertilisers viz, [(control; 100% NPK (120:90:60 kg ha−1); 75% NPK + 5 tonne biochar; 50% NPK + 10 tonne biochar; 25% NPK + 15 tonne biochar and 20 tonne biochar ha−1)] on wheat yield and soil properties under different management practices [(raised bed (more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The conversions of phosphorus through mineralization and immobilization processes alter the availability of P in topsoil and affect its supply to plants. According to different crop scientists, the average recovery of phosphorus from phosphate fertilizer is less than 45 percent in the first year of application [5]. It makes numerous kinds of fixations with others elements such as aluminum, iron and calcium and converts into an insoluble P compound [6], depending upon the soil pH.…”
Section: Introductionmentioning
confidence: 99%
“…The conversions of phosphorus through mineralization and immobilization processes alter the availability of P in topsoil and affect its supply to plants. According to different crop scientists, the average recovery of phosphorus from phosphate fertilizer is less than 45 percent in the first year of application [5]. It makes numerous kinds of fixations with others elements such as aluminum, iron and calcium and converts into an insoluble P compound [6], depending upon the soil pH.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal contamination of agricultural lands has become an emerging environmental issue worldwide ( Saleem et al., 2020b ; Saleem et al., 2020f ; Afzal et al., 2021 ; Amna Ali et al., 2021 ; Farooq et al., 2022 ). This problem is becoming a serious threat to humans and animals because of the entry of heavy metals in the food web ( Salam et al., 2022 ; Tariq et al., 2022 ; Ullah et al., 2022 ). High concentrations of heavy metals significantly reduce plant productivity and crop yields ( Javed et al., 2020 ; Rana et al., 2020 ; Saleem et al., 2020c ; Alsafran et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…A few waste-derived fertilizer products have also been discovered to contain high levels of dioxins (measured in parts per trillion) in their composition (Abubakari et al 2017). Phosphorus is widely used in fertilizer production; nevertheless, its widespread use contributes significantly to the accumulation of heavy metals in soil (Alam et al 2022;Alatawi et al 2022b;Sarwar et al 2022;Ullah et al 2022). It has been demonstrated that water-insoluble phosphorus fertilizers cause the formation of Phosphate rocks, which play a key role in the immobilization of metals in soils via metal phosphate precipitation (Saleem et al 2022a).…”
Section: Fertilizers As a Source Of Heavy Metalsmentioning
confidence: 99%